Challenges in environmental ethics - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 2005)
Twelve cases in environmental ethics, videoclips and commentary. An antelope fence, hunters ethics, bear hunting, whales in Alaska, drowning bison in Yellowstone, euthanized elephant calf, drive-through sequoia, tree-spiking, San Clemente goats, old growth forests, Yellowstone fires, planet Earth.
Dr. Rolston presents a commentary on environmental ethics by discussing the following twelve videoclips: 1. Antelope Fence, Red Rim, Wyoming; 2. Hunter's Ethic, Colorado; 3. Bear Hunting; 4. Drowning Whales in Alaska; 5. Drowning Bison in Yellowstone National Park, Wyoming; 6. Elephant Calf Euthanized, Botswana; 7. Wawona Tree, Yosemite National Park, California; 8. Tree Spiking; 9. San Clemente Goats, San Clemente Island, California; 10. Old Growth Forest, Pacific Northwest, USA; 11. Yellowstone Fires, Yellowstone National Park, Wyoming; 12. Home Planet: Earth.
Presentation shot at Tamasag, CSU facility near Bellvue, Colorado, February 18, 2005.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: environmental ethics; nature; plants; humans; conservation; ecology; ecosystems; coal mining; development; animal rescue; intervention; mercy killing; living things; wildlife; endangered species; Earth